Technical Developments for Rehabilitation of Mobility - Dohle, Christian; Müller, Friedemann; Stephan, Klaus Martin (Neurology International Open, 2017)
Technically assisted rehabilitation of mobility after stroke has been well established for several years. There is good evidence for the use of end-effector devices, exoskeletons and treadmill training with and without body weight support. New developments provide the possibility for functional training during mobilization, even in intensive care units. Mobile exoskeleton devices have been developed, but their clinical effects need still to be evaluated. All devices should not only focus on increasing the number of repetitions, but also include motivational aspects such as virtual reality environments. Hygienic aspects impose a special challenge. All devices should be integrated into a rational and clearly-defined therapy concept.
Keywords: technically-assisted rehabilitation; mobility; effectiveness; hygiene; robotics